A Logistic Curve in the SIR Model and Its Application to Deaths by COVID-19 in Japan - Saito, Takesi; Shigemoto, Kazuyasu (European Journal of Applied Sciences, 2022)
Approximate solutions of SIR equations are given, based on a logistic growth curve in the Biology. These solutions are applied to fix the basic reproduction number α and the removed ratio c, especially from data of accumulated number of deaths in Japan COVID-19. We then discuss the end of the epidemic. These logistic curve results are compared with the exact results of the SIR model.